Leadership in times of crisis: Local government responses to fuel shortages in Bengkulu Province - Muhammad Adnan Al Kadly Kanedy (Green Governance: Exploring Politics, Social Justice, and the Environment, 2025)
Background: This study investigates the leadership response of the Bengkulu Provincial Government to the 2025 fuel shortage crisis, using the theoretical framework of crisis management and adaptive leadership. The crisis revealed structural weaknesses in Indonesia's centralized fuel governance system, as well as the limited anticipatory capacity at the local level. Methods: The research applies a qualitative method with document analysis, drawing on policy documents, media reports, and statistical data. The analysis is guided by Boin et al.'s five tasks of crisis leadership: sense-making, decision-making, meaning-making, terminating, and learning. Findings: Findings indicate that the local government's response was predominantly reactive and characterized by ad hoc decisions, limited coordination, and weak narrative framing. While symbolic actions such as the work-from-home policy helped to mitigate immediate public dissatisfaction, deeper issues such as logistical vulnerabilities at Pulau Baai Port and the absence of contingency reserves remained unaddressed. Furthermore, the lack of transparent communication platforms hindered public trust and accountability. The crisis termination was premature and unaccompanied by institutional learning or structural reforms, reflecting a failure to transition from short-term crisis response to long-term resilience planning. Conclusion: This study concludes that the Bengkulu case highlights the urgent need for decentralized energy governance, investment in predictive infrastructure, and the institutionalization of crisis learning mechanisms. Local governments must be empowered not only to manage operational disruptions but also to initiate reforms that reduce systemic vulnerability and improve crisis preparedness in peripheral regions. Novelty/Originality of this Article: This study uniquely applies the five tasks of crisis leadership to analyze a provincial government’s response to a fuel crisis, revealing critical gaps in decentralized governance and institutional learning often overlooked in Indonesian energy policy research.